Karakterisasi asam lemak minyak hati cucut (Centrophorus sp.) yang diekstraksi dengan metode dry rendering - Anhar Rozi; Nabila Ukhty; Ikhsanul Khairi; Irhamdika Irhamdika; Ade Irma Meulisa; Stephanie Bija (Jurnal Pengolahan Hasil Perikanan Indonesia, 2019)
Shark liver by-product has potential to be reprocessed into valuable products. The aim of this study was to utilize byproduct of shark in West Aceh to become fish oil. The oil was extracted using an oven with different temperatures (40, 50, and 60°C) for 8 hours. The results of proximate analysis showed that the protein content was 15.71 ± 0.13%, fat was 14.70 ± 1.66%, moisture was 58.11 ± 0.57%, ash was 1.19 ± 0.006, and carbohydrate was 10.30 ± 2.12%. The yield of liver oil reached 90% and contained omega-3 fatty acids including EPA and DHA. The heavy metal residue of shark liver oil was still below the threshold set by BSN, with an exception for Cd with 0.892 ppm. Saturated fatty acid (SFA) was 34.75% with palmitic acid as the dominant. Mono unsaturated fatty acid (MUFA) content was 12.86% with oleic acid was the dominant. Poly unsaturated fatty acid (PUFA) content was 17.29% with DHA as the main component. The highest yield of shark liver oil was obtained from extraction at 60°C (49.4%). The heavy metal residue of the oil was still below the threshold, except for Cu. The 50°C extraction temperature was considered as the best treatment resulting fish oil with 41.67% SFA, 14.37% MUFA, and 21.82% PUFA. Keywords: extraction, fatty acid, Shark liver by-product has potential to be reprocessed into valuable products. The aim of this study was to utilize byproduct of shark in West Aceh to become fish oil. The oil was extracted using an oven with different temperatures (40, 50, and 60°C) for 8 hours. The results of proximate analysis showed that the protein content was 15.71 ± 0.13%, fat was 14.70 ± 1.66%, moisture was 58.11 ± 0.57%, ash was 1.19 ± 0.006, and carbohydrate was 10.30 ± 2.12%. The yield of liver oil reached 90% and contained omega-3 fatty acids including EPA and DHA. The heavy metal residue of shark liver oil was still below the threshold set by BSN, with an exception for Cd with 0.892 ppm. Saturated fatty acid (SFA) was 34.75% with palmitic acid as the dominant. Mono unsaturated fatty acid (MUFA) content was 12.86% with oleic acid was the dominant. Poly unsaturated fatty acid (PUFA) content was 17.29% with DHA as the main component. The highest yield of shark liver oil was obtained from extraction at 60°C (49.4%). The heavy metal residue of the oil was still below the threshold, except for Cu. The 50°C extraction temperature was considered as the best treatment resulting fish oil with 41.67% SFA, 14.37% MUFA, and 21.82% PUFA.